Succession Planning and Leadership Development in Nursing: A Bibliometric Analysis (2000-2023) - Azza K. Al Hajri (Wiley, 2024)
Succession planning is a commonly employed term in business strategy, referring to the systematic process of transferring leadership responsibilities to another employee to ensure the seamless continuity of an organization's operations. Today, this concept has acquired importance in various industries, including healthcare, with a specific focus on nursing. Several factors led nurse managers to consider preparing potential leaders for primary leadership roles due to the shortage of nurses, significantly impacting healthcare services and patient safety. Because of the importance of this topic, this present bibliometric analysis aims to analyze research studies conducted on succession planning and leadership development in nursing from 2000 to 2023 to identify research trends, key themes, and the evolution of research during this period. The Elsevier Scopus database was utilized for this analysis. This methodology identified (n = 326) journal studies based on the predefined keywords and timeframe. The data derived from this bibliometric analysis offers a robust foundation for conducting a systematic review, enabling a comprehensive synthesis and evaluation of the evidence in this significant field of study.